Asistencia a mujeres embarazadas con VIH/sida en Fortaleza, Ceará, Brasil - Damasceno, Karla Santana Azevedo; Alves dos Prazeres, José Carlos; Araújo, Maria Alix Leite; Valdanha Netto, Américo [UNESP] (My University, 2013)
The objective of this study is to analyze the perinatal results of the prophylactic measures adopted in the prevention of the vertical transmission of HIV. The study was carried out using the medical records of 168 women with HIV and their newborns in a public maternity unit of Fortaleza, in the state of Ceará, from 2005 to 2009. The data was obtained between the months of March and September 2010 and was analyzed using the program SPSS 10.0. The women diagnosed before pregnancy received timely care that permitted them an effective antiretroviral therapy and a greater number of check-ups (p<0,05). Antiretroviral therapy was administered to 97.6% of the pregnant women, and triple therapy in 88.7%. AZT was administered intrapartum in 95.2% of the women and oral AZT in syrup to 100% of the newborns. Birth by cesarean section was predominant (92.8%) and was associated to the intrapartum use of AZT when compared to vaginal birth (p<0.001). Cesarean section favored intrapartum administration of AZT.
Medical care provided to pregnant women with HIV/AIDS in Fortaleza, Ceará, Brazil
Keywords: AIDS serodiagnosis; Brazil; Delivery; HIV infections/prevention & control; Obstetric; Prenatal care